93 Ejection Fraction by Cardiovascular Magnetic Resonance Predicts Adverse Outcomes Post Aortic Valve Replacement. (31st May 2014) - Vassiliou, Vassilis; Chin, Calvin; Perperoglou, Aris; Tse, Gary; Ali, Aamir; Raphael, Claire; Jabbour, Andrew; Newby, David; Pennell, Dudley; Dweck, Marc; Prasad, Sanjay
Abstract : Introduction: Predicting prognosis following aortic valve replacement (AVR) in patients with aortic stenosis (AS) remains challenging. Current guidelines recommend that surgery should be offered when ejection fraction (EF) is <50%. We sought to investigate the prognostic significance of EF calculated by cardiovascular magnetic resonance (CMR) in the long term survival of patients following AVR. Methods: 80 patients (69 ± 11 years old at time of surgery; 55 male) scheduled for AVR underwent CMR assessment. 52 patients had severe AS (area <1cm 2 ), 28 patients had moderate AS (area 1.0–1.5cm 2 ) and other qualifying reasons for AVR. 44 patients had additional coronary artery disease.Patients were categorised into three groups according to EF prior to surgery: Group 1 (EF <50%; n = 26), Group 2 (EF of 50–70%; n = 26) and Group 3 (EF >70%; n = 28). A median 5.0 ± 1.8 years follow-up was completed using the National Strategic Tracing Scheme and hospital notes. Results: Univariate analysis of all cause mortality using the Kaplan-Meier estimator demonstrated significantly higher mortality in patients with Group 1 (EF <50%) compared to those in group 3 (EF >70%; .03).There was no statistical difference between group 2 (EF of 50–70%) and the remaining 2 groups. Conclusion: Pre-operative EF is a significant predictor of mortality following AVR. Patients with EF <50% have the worst prognosis whereas those with EF >70% have the best prognosis. We aim to incease the sample size to determine whether a progressive decrease in EF per se even when above 50% should initiate consideration for AVR.